Effect of magnetically treated water on the Albumin in some body organs of common carp fish Cyprinus carpio L. - F. J. Mohammed (Tikrit Journal of Pure Science)
The fish common carp Cyprinus carpio L. were exposed to the magnetically treated water with different magnetic intensities (750, 1500 and 3000 Gauss) for a period of 2, 4 and 8 days.